Unveiling the biochemical potential of Acacia jacquemontii as a therapeutic agent in parkinson’s disease: A multi-model in Vitro, In Vivo, and In Silico Study - Andleeb Asghar; Tahir Ali Chohan; Aisha Qayyum; Sibghat Mansoor Rana; Khuram Ashfaq; Hafiz Muhammad Mazhar Asjad; Talha Ali Chohan; Abdulwahab Alamri; Ahmed Alsolami; Fawwaz F. Alshammrie; Hammad Saleem; Sirajudheen Anwar (PLoS ONE, 2026)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder marked by oxidative stress, inflammation, and the degeneration of dopaminergic neurons. Current treatments focus more on symptom management rather than disease prevention. Acacia jacquemontii , rich in antioxidants, may offer a novel therapeutic approach for PD. This study aims to investigate the phytochemical composition, antioxidant capacity, anti-Parkinsonian efficacy, and in-silico validation of Acacia jacquemontii methanol extract (AJME) using liquid chromatography-mass spectrometry (LC-MS). Secondary metabolites were identified, and total alkaloid, phenolic, and flavonoid contents were quantified. LC-MS was used for detailed compound profiling. Antioxidant activity was evaluated using the DPPH assay. In vivo tests on Wistar rats modeled PD through haloperidol administration. AJME’s anti-Parkinsonian effects were assessed via histological, biochemical, and behavioral analyses. In-silico techniques, including molecular docking, structural interaction fingerprinting, ADME prediction, DFT, MESP studies, and molecular dynamics (MD) simulations, were employed to understand AJME molecules’ binding interactions and electronic properties. In vivo , AJME improved locomotor activity, memory, exploratory behavior, oxidative stress markers (SOD, CAT, GSH, MDA), and neurotransmitter levels (dopamine, noradrenaline, serotonin) in rats. In-silico validation identified CP21 as a potent ligand. MD simulations indicated stable AJME-AChE complexes, with enhanced binding affinity through hydrophobic and van der Waals interactions. A. jacquemontii exhibits significant phytochemical, antioxidant, and anti-Parkinsonian properties. The combined in vitro, in vivo , and in silico studies, supported by LC-MS analysis, suggest that AJME could provide a promising option for developing new therapeutic approaches for PD. However, clinical evaluation is necessary to establish its efficacy and safety in human subjects.